Mediating Role of Organizational Justice: Examining the Effect of Transformational Leadership on Citizenship Behavior - Kusairi; Nanang A S; Pujangga Abdillah; Siti Syazwani Zulkuple (University of Merdeka Malang, 2025)
In the healthcare sector, leadership plays a vital role in shaping employee attitudes and behaviors. Organizational citizenship behavior (OCB) is essential for maintaining effective healthcare services, and understanding its driving factors is crucial for hospital management. The aim of this study is to investigate how organizational justice mediates the impact of transformational leadership on the citizenship behavior of nurses. There are 210 questionnaire papers were distributed to nurses who had worked at the Hospital X in Tuban, Indonesia, for more than a year in order to collect the data. A total of 205 completed questionnaires were returned by nurses who had worked for more than a year. According to this study, transformational leadershiprganizational justice as well as OCB. Furthermore, organizational justice is a crucial predictor in enhancing citizenship behavior of nurses. The relationship between transformative leadership and OCB can be mediated by organizational justice, as anticipated. This study suggests the leaders constantly motivate nurses to attach importance to the team and organization and encourage organizational justice because they who show OCB many times tend to be inspired by motivating leadership and feel that leaders have made a fair decision and treated them fairly.